Motivasi Semangat Belajar Mahasiswa Tri Pens dengan Sistem Daring dalam Persepsi Ihsan - Fahreza, Rafi (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
Islam obliges its people to seek knowledge and become knowledgeable and educated people. However, in this pandemic era, everything is done online, including in terms of learning. this makes students who study have more obstacles such as connections, devices, or other distractions so that they can make students less motivated in studying. In doing something, one must have the motivation to do that so that it can be a driving force in achieving goals. The importance of motivation for the learning spirit of Internet Engineering Technology Electronic Engineering Polytechnic Institute of Surabaya students with an online system in Ihsan's perception is that it can make students more enthusiastic in learning, can make students more enthusiastic in achieving their goals and can also make students more trustworthy in studying